The profile of the victim and the type of crime as determining factors for non-reporting in Ecuador - María Antonia Machado Arévalo; Francisco Alexander Arias Pallaroso; Cristian Joseph Chuqui Mainato; Andrés de Jesús Ramírez Chica; Dolores Catalina Sucozhañay Calle (Oñati Socio-Legal Series)
Latin America reveals the highest rates of non-reporting of crime worldwide, even more so in countries like Ecuador where non-reporting is recorded in 80% of criminal events. Studies on victims and non-reporting are still scarce and have focused on victimization rates; in addition, there is a theoretical gap on non-reporting from its primary causalities. This study analyzes it from the observation of the socio-demographic profile of the victims and the type of crime perpetrated as influencing factors. Using quantitative research methods, the III Survey of Victimization and Perception of Citizen Security of Cuenca, Ecuador, 2016 was analyzed, which shows a profile of a victim who does not report linked to exclusion, poverty and inequities and a pattern of less reported crimes in thefts, robberies and extortion, factors that must be recognized in order to focus victimological public policy efforts.